KEHIDUPAN SOSIAL EKONOMI PEREMPUAN PEKERJA PENYAPU JALAN DI KOTA SIAK KABUPATEN SIAK - Arin Ramayani Br. Pinem; Jonyanis " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research was conducted at Kota Siak Kabupaten Siak. The purpose of this research is to know the socio-economic life of women road sweeper workers at Kota Siak Kabupaten Siak. The focus of this research is to analyze the factors that encourage women street sweepers to work at Kota Siak Kabupaten Siak. The technique of determining samples in a purposive sampling and set the number of samples as many as 5 people. The author uses qualitative descriptive method and Instrument data is observation, interview and documentation.Research conducted to find: social life, happening relationships with children, but not with a husband. The research subject husband all support the wife's job as a street sweeper. Relationships with children stretch because the subject of research to rarely communicate more with children due to work schedules. Not only the relationship with the family, but also the relationship with the community. Research subjects, in relation to the neighbors can be said very far. Prior to working as a street sweeper, the subject of routine research carried out the obligations of community members such as mutual assistance, religious and other activities, but after working as a street sweeper, the subject of the study was more alienated from his social life. Although not all, some people consider the road sweeper job is a low status job. The study, which focused on the economic life of the research subjects, found that not all husband and wife income were able to meet the economic needs of the study subjects. To that end, the subject of research looking for such initiatives should be frugal and save. To cover the economic shortage, the research subjects have their own house so no need to spend more money to pay rent and also have a small garden around the house, so when unable to buy side dishes, research subjects can take it from the garden. The study found that the reason women work is because of the demands of life that cause economic pressure, in addition to working also become a means to overcome saturation for the subject of research. Although not all societies support the research subject's work as a street sweeper, the family continues to provide full support for the research subject. Keywords: Socio-Economic, Factor, Role, Perception